Exploration of biophoton characteristics of fresh Isatis indigotica fort leaves under salt and drought stresses and the feasibility analysis for the quality prediction of Isatidis Folium - Zhiying Wang; Zhiying Wang; Baorui Cao; Baorui Cao; Yueyue Ma; Weifan Xu; Jialei Fu; Zhongwen Zhang; Jinxin Du; Tingting Deng; Jingxiang Pang; Meina Yang; et al. (Frontiers in Plant Science)
IntroductionIsatidis Folium, derived from the dried leaves of Isatis indigotica Fort, has been used for centuries as a traditional Chinese herb with antibacterial and antiviral properties. However, both the cultivation conditions and the growth status of Isatis indigotica Fort have been negatively affected by climatic and environmental degradation, which has made it challenging to accurately assess the quality of Isatidis Folium. The current quality control system for Isatidis Folium lacks precision and comprehensive identification indices, and importantly, the cultivation process has not been integrated into this system.MethodsIn this study, we proposed a novel method to distinguish between different stress subtypes in Isatis indigotica Fort based on biophoton emission and attempted to explore the potential relationship between the biophoton characteristics of fresh Isatis indigotica Fort leaves and the quality of Isatidis Folium. The delayed luminescence (DL) and spontaneous photon emission (SPE) characteristics of fresh Isatis indigotica Fort leaves under different stress conditions were detected using a biophoton detection system. An attempt was made to differentiate samples subjected to various stress treatments using biophoton characteristic parameters. Additionally, the content of active ingredients was determined by ultra-high performance liquid chromatography, and the inhibitory activity against Escherichia coli and Staphylococcus aureus was evaluated to identify the quality of Isatidis Folium. Several physiological indicators of fresh Isatis indigotica Fort leaves, including the photosynthetic pigment content, relative electrical conductivity, and reactive oxygen species production rate were also determined.ResultThe differences in physiological indices, active ingredient content, and inhibitory activity indicated that the stress conditions significantly inhibited the growth status of Isatis indigotica Fort leaves and the herbal quality. Meanwhile, biophoton characteristic parameters were obtained that could accurately and efficiently distinguish fresh Isatis indigotica Fort leaves between different stress subtypes: initial intensity of DL and counts per second of SPE. Both characteristic parameters were highly correlated with the physiological indicators and quality of Isatidis Folium.DiscussionThis study has preliminarily demonstrated the feasibility of utilizing biophoton detection technology for the quality evaluation of Isatidis Folium during cultivation for the first time and provided an improved method for distinguishing samples of various qualities.